The Effectiveness of Industrial Print Advertisements across Product Categories - Hanssens, Dominique M.; Weitz, Barton A. (Journal of Marketing Research, 1980)
The relationships between 24 print ad characteristics and recall, readership, and inquiry-generation measures of effectiveness are examined for 1160 industrial ads. Both recall and readership are strongly related to format and content characteristics of industrial ads. The relationship between inquiry-generation and ad characteristics is significant but weaker. Some characteristics, such as ad size and position in the magazine, are consistently related to effectiveness across product categories and effectiveness measures. The effects of other characteristics, such as the use of four colors and attention-getting techniques, are specific to the product category and effectiveness measure. In addition to these substantive findings, methodological issues in model development and testing are presented.